A Collaborative System Design for Avoiding and Removing the Unexpected Obstacles Encountered during Wheelchair Navigation - Kirmizibiber, Abdullah; Gokgoz, Turkay (MDPI, 2024)
In this study, we designed a system that cooperates with users to always provide the most up-to-date map and the most suitable route and to cooperate with disability units to ensure that unexpected obstacles on the route are removed. It is believed that this system will contribute to (1) eliminating obstacles more quickly and preventing other people with disabilities from being aggrieved until the obstacles are removed; (2) increasing awareness of the responsibility towards people with disabilities in society; (3) greater integration of people with disabilities; and (4) increasing the economic and social welfare of society. The design process includes analysis of the current situation, data acquisition, web mapping, mobile application development, and experimental testing phases. The system successfully passed the tests. However, the optimum level of expected benefits of the system depends on users' consistent use of the mobile application complaint tool and authorities' consistent evaluation of the complaints received. As the number of mobile application users increases, the number of complaints will gradually increase, yet after a while, as the awareness and sensitivity of society on this issue gradually increase, the number of complaints will gradually decrease, and the expected benefits will be achieved.
Keywords: collaboration; system design; mobile application; wheelchair navigation; questionnaire; MAP-MATCHING ALGORITHM; PEOPLE; Chemistry; Engineering; Materials Science; Physics